Measuring social support in psychiatric patients and controls: Validation and reliability of the shortened Close Persons Questionnaire. (September 2019) - Hanssen, Denise J.C.; Rabeling-Keus, Inge M.; Lucassen, Peter L.B.J.; Naarding, Paul; van den Brink, Rob H.S.; Comijs, Hannie C.; Penninx, Brenda W.J.H.; Oude Voshaar, Richard C.
Abstract: Although previous studies have underlined the protective role of social support for physical and psychological health, no self-report questionnaires are validated for measuring social support in large-scale psychiatric epidemiological studies. In the current study, we aim to validate the shortened version of the Close Persons Questionnaire (CPQ), a self-report questionnaire that is administered twice to measure social support received from the partner (CPQ-p) as well as from a close friend/family member (CPQ-f). Data of psychiatric patients (n = 1891) and controls (n = 1872) from three Dutch epidemiological studies that assessed determinants of psychopathology were used to validate the shortened CPQ. This included determining factor structure and reliability for the different scales. Using multigroup confirmatory factor analyses, a four-factor model proved to be the best fitting model for both the CPQ-p and CPQ-f. The resulting subscales -emotional support, practical support, negative support experiences, inadequacy of support-showed moderate to good reliability for both the CPQ-p and the CPQ-f, and were all correlated with other social measures in the expected directions. The shortened version of the CPQ proves to be a valid and reliable measure of social support for both psychiatric patients and controls. Further research is needed to assess usability of the shortened version of the CPQ for clinical practice.